2005
DOI: 10.1249/01.mss.0000175090.49048.41
|View full text |Cite
|
Sign up to set email alerts
|

Electromyostimulation Training Effects on Neural Drive and Muscle Architecture

Abstract: We concluded that the voluntary torque gains obtained after EMS training could be attributed to both muscular and neural adaptations. Both changes selectively involved the monoarticular vastii muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
170
3
6

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 198 publications
(197 citation statements)
references
References 29 publications
(55 reference statements)
16
170
3
6
Order By: Relevance
“…Details on the NMES protocol can be found in Gondin et al (12). The protocol had been successfully used in previous studies to increase knee extensor muscle strength (13).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details on the NMES protocol can be found in Gondin et al (12). The protocol had been successfully used in previous studies to increase knee extensor muscle strength (13).…”
Section: Methodsmentioning
confidence: 99%
“…NMES represents an obligatory choice for training in patients who cannot perform voluntary contractions, such as those with spinal cord lesions (10), or in patients immobilized for fractures or following ligament reconstruction surgery (42). It is well established that NMES leads to significant increases in muscle mass and maximal voluntary strength (13,26,39).The effects of NMES on oxidative metabolism appear rather controversial. At molecular level, Perez et al (36) reported a higher succinic dehydrogenase activity after NMES training, whereas both citrate synthase and phosphofructokinase activities were unchanged.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…First, it provides a reproducible experimental model in which physiological adaptations, such as myofiber hypertophy and muscle strengthening 6 , angiogenesis [7][8][9] , growth factor secretion [9][10][11] , and muscle precursor cell activation 12 are well documented. Such physiological responses may be carefully titrated using different parameters of stimulation (for Cochrane review, see 13 ).…”
mentioning
confidence: 99%